DEVELOPMENT OF PORTABLE PALM OIL HARVESTER BASED ON 21 VOLT DC MINI CHAIN SAW ELECTRIC MOTOR - Rachmad Ikhsan; Rouhillah; Kurniawati (PT. Radja Intercontinental Publishing, 2024)
The objective of this research was to create a portable palm oil harvester using a mini chain saw electric motor. The focus was on the design, construction, and performance trials of the harvester. The palm oil industry requires efficient harvesting methods to keep up with the increasing demand. Traditional harvesting techniques are time-consuming, labor-intensive, and pose risks to workers. This research aimed to address these challenges by developing a more compact, lightweight, and efficient harvester using a mini chain saw electric motor. The study included ergonomic design, prototype construction, strength and durability testing, and performance evaluation under various field conditions. The final test results for the Portable Oil Palm Harvester showed an average cutting time of 21.4 seconds in the initial position (3m tube position) and 37.4 seconds in the maximum position (5m tube position) for oil palm harvesters weighing around 6kg.